Preparation method of low-cost high-entropy alloy aerogel electrocatalytic material

Through self-assembly technology and freeze-drying process, low-cost, high-entropy alloy aerogel electrocatalytic materials are prepared, solving the problems of scarce, poor stability and insufficient catalytic activity of existing catalyst resources, and achieving efficient, low-cost and versatile electrocatalytic performance.

CN119581587AActive Publication Date: 2025-03-07NANJING TECH UNIV

Patent Information

Application Number
CN202411678051.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Existing fuel cell catalysts have problems such as scarce resources, poor stability and insufficient catalytic activity, and it is difficult to meet the needs of high efficiency, low cost and versatility.

Method used

Self-assembly technology combined with freeze-drying technology is used to prepare low-cost, high-entropy alloy aerogel electrocatalytic materials. Through freeze-thawing technology and a co-precursor solution with low precious metal load, HEAs aerogel with high specific surface area and high porosity is formed.

Benefits of technology

It has achieved low-cost, high catalytic activity, versatility and high stability, which significantly improves electrocatalytic performance and has the potential for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581587A_ABST
    Figure CN119581587A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation processes of nano porous materials, and relates to a preparation method of a low-cost high-entropy alloy aerogel electrocatalytic material. The preparation method comprises the following steps: uniformly stirring and mixing five metal salt solutions, adding a reducing agent, and finally obtaining the low-cost, high-activity and multifunctional high-entropy alloy aerogel material by virtue of a freeze-thawing technology, solvent replacement and a freeze-drying method. The invention has the advantages of low material cost and convenient process, and also has the advantages of low energy consumption, lower cost, multifunction integration, higher stability and easy realization of large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of aerogel material preparation technology, and specifically relates to a method for preparing a low-cost high-entropy alloy aerogel electrocatalytic material by combining a self-assembly technology with a freeze-drying process. Background Art

[0002] Fuel cells have the advantages of high theoretical energy density, environmental friendliness and low cost, and have become one of the best alternatives to traditional energy. Among the reaction processes involved in many fuel cells, oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) both occupy an important position, and their reaction efficiency dominates the performance of the battery charging and discharging process. Among them, ORR is a four-electron proton coupling process. The chemical reaction of this process is complex and difficult to control, and the kinetic reaction is slow. Therefore, it is necessary to use an efficient ORR catalyst to promote the reaction process. The current commercial catalysts are mainly based on Pt / C, and the defects of this catalyst such as scarce resources, poor stability and insufficient catalytic activity limit its wide application. Therefore, it is of great research significance to develop an electrocatalyst that has high catalytic activity, high stability and low cost.

[0003] Aerogel is a nanoporous material composed of nanoparticles. It has unique properties such as high specific surface area, high porosity and ultra-low packing density. It has received extensive attention in the fields of thermal insulation, adsorption, catalysis and sensing. The high specific surface area and highly interconnected pores of aerogel materials can expose more reactive sites, and at the same time facilitate full contact between the catalyst and the electrolyte, thereby improving the reaction efficiency. Therefore, aerogel is an ideal electrocatalytic carrier.

[0004] High entropy alloys (HEAs) are composed of 5 or more elements with similar atomic ratios (5%-35%) and have attracted widespread attention due to their excellent mechanical and chemical properties. In addition, the cocktail effect of HEAs can effectively provide multiple sites for the adsorption of different intermediates, and the electronic structure of the active site can be finely adjusted by the surrounding atoms to obtain superior catalytic performance. He (Energy Storage Materials, 2023, 58, 287-298.) et al. synthesized CrMnFeCoNi HEAs based on a low-temperature solution method. Due to the presence of twin defects, the occurrence of large lattice distortion, and the electronic synergy between different components, the energy barrier of the OER rate-determining step is reduced, making it 10mA / cm 2 At a current density of 2.5 Å, the overpotential is 265 mV and the Tafel slope is 37.9 mV / dec, which is much higher than that based on RuO 2properties of standard commercial catalysts. However, the HEAs electrocatalysts reported so far are mainly low-dimensional. In order to further expose more active sites, it is of great significance to realize HEAs with unique three-dimensional structures. HEAs aerogels have a hierarchical layered porous structure, which allows effective mass transfer in the pores and has smaller diffusion resistance and easier access to active sites (crystal surface defects and crystal surface active species, etc.). The HEAs aerogel network skeleton is mainly composed of interconnected precious metal nanounits with a size of several nanometers, which is the optimal range of catalyst size for electrochemical catalytic processes such as ORR, methanol oxidation reaction (MOR) and OER. Ju (Chemical Engineering Journal, 2023, 473, 145347) et al. synthesized PtBi by combining co-reduction method with freeze-drying technology. 1.5 Ni 0.2 Co 0.2 Cu 0.2 HEAs aerogels show aerogel structures with large specific surface area and high porosity. 1.5 Ni 0.2 Co 0.2 Cu 0.2 The mass activity of HEAs is 4.19 A·mg Pt -1 , long-term stability (>0.33A·mg after 10 3600s stability tests) Pt -1 ) is superior to binary Pt-based alloys and commercial Pt / C. However, the above studies have only achieved a certain degree of breakthrough in single function, and the content of precious metals is relatively high. Therefore, it is still a great challenge to combine the advantages of low cost, high catalytic activity, multifunctionality and high stability to achieve single-phase high-entropy alloy aerogel electrocatalysis. Summary of the invention

[0005] The purpose of the present invention is to improve the high price, poor stability, single performance and insufficient activity of existing electrocatalytic materials, and to provide a method for preparing a low-cost high entropy alloy aerogel electrocatalytic material. A low noble metal loading, high activity and multifunctional HEAs aerogel electrocatalyst is prepared by freeze-thawing technology combined with freeze drying. The method has simple raw materials and processes, low energy consumption, and controllable structure. The prepared aerogel material has the characteristics of low density, high specific surface area and high porosity, which has positive significance for realizing the application of HEAs aerogel in the field of electrocatalysis.

[0006] The object of the present invention is achieved by the following method: a method for preparing a low-cost high-entropy alloy aerogel catalytic material, the specific steps of which are as follows:

[0007] (1) dissolving five metal salts in equal amounts in deionized water, stirring at 20 to 40° C. to uniformly mix, adding a weighed reducing agent and stirring for 10 to 30 minutes to prepare a co-precursor solution;

[0008] (2) freezing the co-precursor solution obtained in step (1) in liquid nitrogen for 2 to 20 minutes, and then thawing in a water bath at 10 to 40° C.;

[0009] (3) stirring the sample thawed in step (2) for 0.1 to 2 hours to form an overall gel;

[0010] (4) removing impurities from the wet gel obtained in step (3), washing with deionized water 3 to 8 times, each time interval of 6 to 18 hours;

[0011] (5) freezing the HEAs wet gel washed in step (4) with liquid nitrogen for 2 to 15 minutes, and then freeze-drying the gel to obtain a HEAs aerogel;

[0012] Wherein: in step (1), the molar concentration of the five metals after the metal salts are dissolved in deionized water is 0.005-0.015 mmol / mL; the metal salts are any four metal salts of platinum salt, copper salt, nickel salt, cobalt salt, manganese salt or iron salt mixed with palladium chloride; in step (2), the molar ratio of the five metal salts to the reducing agent is 1:(1-5).

[0013] Preferably, the platinum salt described in step (1) is one of chloroplatinic acid, platinum nitrate or platinum sulfate; the copper salt is one of copper chloride trihydrate, copper nitrate pentahydrate, copper sulfate or copper carbonate; the nickel salt is one of nickel chloride hexahydrate, nickel nitrate, nickel sulfate or nickel nitrite; the cobalt salt is one of cobalt chloride hexahydrate, cobalt acetate, cobalt sulfate or cobalt nitrate; the iron salt is one of ferric chloride hexahydrate, ferric nitrate, ferric sulfate, ferrous sulfate or ferric hydroxide; the manganese salt is one of manganese chloride, manganese sulfate, manganese chromate or manganese carbonate.

[0014] Preferably, the reducing agent in step (1) is sodium borohydride, potassium borohydride, lithium borohydride or lithium aluminum hydride, or a mixture of two or more thereof.

[0015] Preferably, the stirring speed when adding the reducing agent in step (1) is 200 to 1300 r / min.

[0016] Preferably, the stirring speed in step (3) is 200 to 1500 r / min.

[0017] Preferably, the freeze-drying temperature in step (5) is -60 to -5°C and the drying time is 8 to 40 hours.

[0018] Beneficial effects:

[0019] The method of the present invention and a low-cost HEAs for electrocatalysis prepared by the method have the following characteristics:

[0020] (1) Simple process, low cost and low energy consumption. Using freeze-thaw technology and co-precursors with low noble metal loading, HEAs aerogel can be obtained by low-cost and safe freeze-drying.

[0021] (2) The material has a low precious metal loading density, low cost, and combines high catalytic activity, high stability, and multifunctionality.

[0022] (3) The HEAs aerogel prepared by this method exhibits extremely excellent electrocatalytic activity and stability in a variety of electrocatalytic fields, which has positive significance for the industrialization and practical application of HEAs aerogel in the field of electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the XRD spectrum of the HEAs aerogel prepared in Example 1;

[0024] Figure 2 The figure shows the application of the HEAs aerogel prepared in Example 2 in zinc-air batteries in the field of electrocatalysis, where (a) is the open circuit voltage of the HEAs aerogel cathode zinc-air battery, (b) is the power density test, (c) is a photo of the zinc-air battery charging a mobile phone, and (d) is a charge and discharge cycle test of the zinc-air battery. DETAILED DESCRIPTION

[0025] Example 1

[0026] 0.075 mmol of palladium chloride, chloroplatinic acid, cupric chloride trihydrate, nickel chloride hexahydrate and ferric chloride hexahydrate in equal molar ratios were dissolved in 15 mL of deionized water, stirred at 20°C to mix evenly, and the reducing agent sodium borohydride was added thereto, the molar ratio of the metal salt to sodium borohydride was 1:1, and stirred at 20°C for 30 min to prepare a co-precursor solution at a stirring speed of 200 r / min; the obtained co-precursor solution was frozen in liquid nitrogen for 2 min, and then waited for thawing in a 10°C water bath; the thawed sample was stirred at 200 r / min for 2 h to form an overall gel; then the solvent replacement of the wet gel obtained above was carried out, and the solvent replacement was carried out 3 times with deionized water, each time with an interval of 18 h; the replaced HEAs wet gel was frozen with liquid nitrogen for 2 min, and then the frozen wet gel was freeze-dried at a drying temperature of -60°C and a drying time of 8 h, and finally a low-cost, high-catalytic-activity and multifunctional PdPtCuNiFe HEAs aerogel is black and blocky. After testing, it was found that its half-wave potential can reach 0.86V vs. RHE, OER overpotential is 357mV, and HER overpotential is 87mV. Figure 1 This is the XRD spectrum of the prepared PdPtCuNiFe HEAs aerogel, and its diffraction peak is a face-centered cubic crystal dominated by Pd.

[0027] Example 2

[0028] 0.227 mmol of palladium chloride, platinum nitrate, copper nitrate pentahydrate, nickel nitrate and cobalt chloride hexahydrate in equal molar ratios were dissolved in 25 mL of deionized water, stirred at 26 ° C to mix evenly, potassium borohydride was added thereto, the molar ratio of metal precursor to potassium borohydride was 1:2.3, and stirred at 26 ° C for 23 min to prepare a co-precursor solution at a stirring speed of 500 r / min; the obtained co-precursor solution was frozen in liquid nitrogen for 6 min, and then waited for thawing in a 22 ° C water bath; the thawed sample was stirred at a speed of 500 r / min for 1.6 h to form an overall gel; then the solvent replacement of the wet gel obtained above was carried out, and the solvent replacement was carried out 4 times with deionized water, each time with an interval of 14 h; the replaced HEAs wet gel was frozen with liquid nitrogen for 6 min, and then the frozen wet gel was freeze-dried at a drying temperature of -38 ° C and a drying time of 18 h, and finally a low-cost, high catalytic activity and multifunctional PdPtCuNiCo HEAs aerogel was obtained. The prepared PdPtCuNiCo HEAs aerogel is black and blocky. After testing, it was found that its half-wave potential can reach 0.88V vs. RHE, the OER overpotential is 307mV, and the HER overpotential is 37mV. Figure 2Performance test of PdPtCuNiCo HEAs aerogel applied to zinc-air battery. The open circuit voltage in Figure (a) can reach 1.48V, and the power density in Figure (b) is 199mW·cm -2 Figure (c) shows a photo of a zinc-air battery powering a mobile phone. After 600 hours of charge and discharge cycles, the efficiency only decreases by 2.7% (Figure (d)). Compared with commercial Pt / C+RuO 2 Electrocatalysts have shown great improvements in all indicators.

[0029] Example 3

[0030] 0.455 mmol of palladium chloride, platinum sulfate, copper sulfate, cobalt nitrate and iron nitrate in equal molar ratios were dissolved in 37 mL of deionized water, stirred at 33 ° C to mix evenly, lithium borohydride was added thereto, the molar ratio of metal precursor to lithium borohydride was 1:3.3, and stirred at 33 ° C for 14 min to prepare a co-precursor solution at a stirring speed of 890 r / min; the obtained co-precursor solution was quickly frozen in liquid nitrogen for 13 min, and then waited for thawing in a 31 ° C water bath; the thawed sample was stirred at 730 r / min for 1.1 h to form an overall gel; then the solvent replacement of the wet gel obtained above was carried out, and the solvent replacement was carried out 5 times with deionized water, each time with an interval of 10 h; the replaced HEAs wet gel was quickly frozen with liquid nitrogen for 11 min, and then the frozen wet gel was freeze-dried at a drying temperature of -20 ° C and a drying time of 28 h, finally obtaining low-cost, high catalytic activity and multifunctional PdPtCuFeCo HEAs aerogel is black and blocky. It has been tested that its half-wave potential can reach 0.89V vs. RHE, OER overpotential is 382mV, and HER overpotential is 22mV.

[0031] Example 4

[0032] Take 0.6 mmol of palladium chloride, chloroplatinic acid, copper carbonate, manganese chloride and ferric sulfate in equal molar ratio and dissolve them in 50 mL of deionized water, stir at 40 ° C to mix them evenly, add lithium aluminum hydride, the molar ratio of metal precursor to lithium aluminum hydride is 1:5, stir at 40 ° C for 10 min to make a co-precursor solution, and the stirring speed is 1300 r / min; the obtained co-precursor solution is quickly frozen in liquid nitrogen for 20 min, and then wait for thawing in a 40 ° C water bath; the thawed sample is stirred at 1500 r / min for 0.2 h to form an overall gel; then the solvent replacement of the wet gel obtained above is carried out, and the solvent replacement is carried out 8 times with deionized water, each time interval is 6 h; the replaced HEAs wet gel is quickly frozen with liquid nitrogen for 15 min, and then the frozen wet gel is freeze-dried, the drying temperature is -5 ° C, and the drying time is 40 h, finally obtaining low-cost, high catalytic activity and multifunctional PdPtCuFeMn HEAs aerogel is black and blocky. It has been tested that its half-wave potential can reach 0.88V vs. RHE, OER overpotential is 386mV, and HER overpotential is 31.7mV.

Claims

1. A method for preparing a low-cost high-entropy alloy aerogel catalytic material, the specific steps of which are as follows: (1) dissolving five metal salts in equal amounts in deionized water, stirring at 20 to 40° C. to uniformly mix, adding a weighed reducing agent and stirring for 10 to 30 minutes to prepare a co-precursor solution; (2) freezing the co-precursor solution obtained in step (1) in liquid nitrogen for 2 to 20 minutes, and then thawing in a water bath at 10 to 40° C.; (3) stirring the thawed sample in step (2) for 0.1 to 2 hours to form an overall gel; (4) removing impurities from the wet gel obtained in step (3), washing with deionized water 3 to 8 times, each time interval of 6 to 18 hours; (5) freezing the HEAs wet gel washed in step (4) with liquid nitrogen for 2 to 15 minutes, and then freeze-drying the gel to obtain a HEAs aerogel; in: In step (1), the molar concentration of the five metals after the metal salts are dissolved in deionized water is 0.005-0.015 mmol / mL; the metal salts are metal salts of any four of platinum salts, copper salts, nickel salts, cobalt salts, manganese salts or iron salts mixed with palladium chloride; in step (2), the molar ratio of the five metal salts to the reducing agent is 1:(1-5).

2. The preparation method according to claim 1, characterized in that The platinum salt described in step (1) is one of chloroplatinic acid, platinum nitrate or platinum sulfate; the copper salt is one of copper chloride trihydrate, copper nitrate pentahydrate, copper sulfate or copper carbonate; the nickel salt is one of nickel chloride hexahydrate, nickel nitrate, nickel sulfate or nickel nitrite; the cobalt salt is one of cobalt chloride hexahydrate, cobalt acetate, cobalt sulfate or cobalt nitrate; the iron salt is one of ferric chloride hexahydrate, ferric nitrate, ferric sulfate, ferrous sulfate or ferric hydroxide; the manganese salt is one of manganese chloride, manganese sulfate, manganese chromate or manganese carbonate.

3. The preparation method according to claim 1, characterized in that The reducing agent described in step (1) is one or a mixture of two or more of sodium borohydride, potassium borohydride, lithium borohydride or lithium aluminum hydride.

4. The preparation method according to claim 1, characterized in that The stirring speed when adding the reducing agent in step (1) is 200 to 1300 r / min.

5. The preparation method according to claim 1, characterized in that The stirring speed in step (3) is 200 to 1500 r / min.

6. The preparation method according to claim 1, characterized in that In step (5), the freeze-drying temperature is -60 to -5°C, and the drying time is 8 to 40 hours.

Citation Information

Patent Citations

  • High-entropy alloy catalyst and preparation method and application thereof

    CN113522308A

  • Preparation method of PdCuFeCoNi high-entropy alloy nanoparticle catalyst applied to water electrolysis

    CN113774422A

  • High-entropy alloy aerogel catalyst as well as preparation method and application thereof

    CN118422249A

  • Multi-principal element alloy (MPEA) nanoparticles

    WO2024040088A1

Cited By

  • Ultra-small high-entropy alloy for lateral flow immunochromatography as well as preparation method and application of ultra-small high-entropy alloy

    CN120190358A

  • Preparation method of non-noble metal medium / high-entropy alloy aerogel electrocatalytic material

    CN121556076A